Analysis of thyristor controlled series compensator in power transmission network by using Bees Algorithm technique / Nurshuhaida Abdul Rahman - Abdul Rahman, Nurshuhaida (2011)
This thesis presents Bees Algorithm (BA) technique to seek the optimum size of Flexible AC Transmission System (FACTS) device which is the Thyristor Controlled Series Compensator (TCSC) in a power transmission network. Fast Voltage Stability Index (FVSI) is used to designate the suitable line location of TCSC installation. Using these methods, the location and size of TCSC are optimized simultaneously and can be used to minimize loss in power transmission network. IEEE 26-bus Reliability Test System (RTS) will be use to investigate the effectiveness of the device. This research varies the loading conditions of the IEEE 26-bus system.